Perceptions of Transformation and Quality in Higher Education: A Case Study of PhD Student Experiences - Groen, Jovan (Université d'Ottawa / University of Ottawa, 2020)
Stemming from increased levels of participation and diversity of the student base (Biggs & Tang, 2011) and growing scrutiny on the quality of university degrees (Crowley, 2013; Marr, 2013), governments have begun putting in place mechanisms to monitor and support quality in higher education. Over the last few decades, a notion of quality that has gained traction in the scholarly community is that of quality in terms of enhancement and transformation (Cheng, 2017; Houston, 2008; Williams, 2016). Guided by the discourses of Transformative Learning Theory (Mezirow, 2000) and transformative conceptions of quality in higher education (Harvey & Green, 1993), this study examined graduate student learning experiences and perceptions of quality. Of further interest was the extent to which these learners were living the intended transformation that academic programs are seeking to foster. Using a multiple case-study design, Seidman’s (2013) three-stage interview protocol served as primary source of data from a sample of six PhD candidates across three faculties. Secondary data sources included collected documents, a reflexivity journal and field notes. A within-case analysis was performed for each case and compared via a cross-case analysis. Institutional characterizations of quality were examined across 25 artifacts via a document analysis. The four principal factors that characterized the PhD candidate learning experience emerged as the significance of intentional individualized guidance, becoming an independent scholar, the importance of social interactions and community, and the transformative nature of learning. Gaps were identified between institutional intent and the learner experience. However, complementarity between discourses of transformation appeared to offer bridges between the macro-level institutional orientation toward fostering student transformation and the micro-level transformative learning experiences lived by students. The dissertation makes conceptual, methodological and empirical contributions to the domains of postsecondary quality and transformative learning. Implications for policy related to quality assurance as well as practice in program development and doctoral supervision are equally shared.
Keywords: Transformative learning; Quality in higher education; Quality as transformation; Student transformation; Student perceptions; PhD learning experience